Different controlled nanostructures of Mn-doped ZnS for high-performance supercapacitor applications. (December 2020) - Hussain, Iftikhar; Mohapatra, Debananda; Dhakal, Ganesh; Lamiel, Charmaine; Mohamed, Saad Gomaa; Sayed, Mostafa Saad; Shim, Jae-Jin
Highlights: Mn was doped on ZnS to make a high-performance supercapacitor electrode material. Huge temperature effect on the morphology of Mn-doped ZnS was observed. Nanosheets exhibited a high capacitance (1905 F/g) and a long cycle life (93%). Mn-doped ZnS//AC ASC showed a high capacitance 140 F/g and lighted 52 LEDs for 150 s. ASC exhibited a high energy density 43.3 Wh/kg and a high power density 6.8 kW/kg. Abstract: Various Mn-doped ZnS controlled nanostructures were synthesized directly on the nickel foam to develop a binder-free, high-performance positive electrode for supercapacitors, where specific energy, specific power, and cycling stability are the crucial parameters. We achieved Mn-doped ZnS based different nanostructures, such as nanosheets, nanoflakes, and nanoneedles just by monitoring the reaction temperature. Among those three morphologies, the nanosheets showed the highest specific capacitance of 1905 F g −1 at a current density of 1 A g −1 and 93.1% capacity retention after 10, 000 cycles in a three-electrode system. An asymmetric supercapacitor (ASC) device was assembled using Mn-doped ZnS nanosheets and activated carbon as a positive and negative electrode, respectively. The ASC device showed a high capacitance of 140 F g −1 (210 C g −1 ), delivered a high specific energy of 43.3 Wh kg −1, and a high specific power of 6.8 kW kg −1 . The ASC device retained 93.3% with excellent coulombic efficiency of 95.7% after 8, 000 cycles. Importantly, two serially connected ASC devices illuminated 52 red light-emitting diodes. This highlights the potential of the Mn-doped ZnS based ASC device for the next generation supercapacitors. Graphical abstract: Image, graphical abstract